Analysis of Identification of Anti-Social Behavior Tendencies in Early Childhood - Arifin, Zainul; Maharani, Putri; Rahmi, Elvi; Zeky, Serpuady (Journal of Islamic Early Childhood Education, 2024)
Antisocial behavior of students found in schools such as being difficult to control, liking to hit, disturbing friends, shouting, being impatient/queuing, not sharing food with friends, liking to fight, and not obeying instructions are caused by various factors both from the child (internal) and external factors (external). The purpose of this study is to explain, examples of behavior and factors that influence antisocial behavior in early childhood aged 5-6 years. The type of research that the author conducted in writing this thesis is in the form of field research with a qualitative descriptive method. As a primary data source in this study were 2 educators. Secondary data sources in this study were the principal and students. Data collection tools in this study were observation, interviews and documentation. Based on the results of the study, it can be concluded that: problems with children's antisocial behavior are: behaving aggressively, behaving shyly, and behaving spoiled. Antisocial behavior in childhood and adolescence is categorized into behavioral disorders, explosive urges, stealing, vandalism, physical and psychological aggression, bullying, running away from home and truancy. Environmental factors are the main causes of antisocial behavior.